Characterization of pack cemented Ni2Al3 coating exposed to KCl(s) induced corrosion at 600 °C. (4th May 2018) - Dahl, K. V.; Slomian, A.; Lomholt, T. N.; Kiamehr, S.; Grumsen, F. B.; Montgomery, M.; Jonsson, T.
Abstract: Oxidation of Ni2 Al3 produced by pack aluminizing of pure nickel was studied with and without 0.10 mg cm −2 KCl(s) deposit in an environment containing 5% O2, 40% H2 O and 55% N2 at 600 °C for up to 168 h. Oxide microstructure and composition was investigated by SEM/EDX, BIB, TEM and GDOES. Oxidised Ni2 Al3 shows minimal weight gain, while adding KCl results in a small weight loss consistent with evaporation of KCl. On the surface of samples exposed to the gas environment only, a 30 nm oxide of Al oxide was present, but where KCl was present as deposit, 50–250 nm thick nodules form that are enriched in K, O and Al.